Membumikan Ilmu Komunikasi di Indonesia (Pembacaan Hermeneutik Gadamerian atas Tulisan-Tulisan M. Alwi Dahlan) - Winartono Winartono; Antoni Antoni; Anang Sujoko (MEDIAKOM : Jurnal Ilmu Komunikasi, 2019)
The emergence of Communication Science in Indonesia was related to the history of this science in Europe and America. The term “communication science” (America’s tradition) was noted to have replaced “Publisistic” (German’s tradition). M. Alwi Dahlan is an important figure behind that. Communication Science then has been developing, but still dominated by applied studies. Whereas to be a discipline, the study of history and philosophy of science shouldn’t be ignored. Furthermore, the development of a science indicates the contribution of it’s intellctuals. Here is the importance of studying Dahlan’s thoughts on communication. The researcher applied a Gadamerian perspective hermeneutic to interpret Dahlan’s writings between 1980-1990s. Based on metanarrative awareness and the spirit of non-Western perspective studies, the researcher has explored them through hermeneutic circle until getting creative meanings (Bildung). The conclusion is that Dahlan’s contribution is contextualizing or bringing Communication Science ‘down to earth’ in Indonesia especially related to development, environment, information-technology, through an eclectic perspective and by which human being as a key resource. Dahlan’s ideas has significance in the development of history and philosophy of Communication Science. Finally, this research suggest further exploration both on Dahlan and related topics. Key Words: M. Alwi Dahlan, Hermeneutics, Gadamerian Perspective, Ilmu Komunikasi